A Comparative Analysis of the Justifications for the McMaster Nuclear Reactor Across its History - Swan, Benjamin; Hall, Alexander (n/a, 2025)
The McMaster Nuclear Reactor (MNR) is one of four nuclear research reactors in Canada and the only one located on a university campus. When construction finished in 1959, it was the seventh university research reactor in the world. Over the interceding decades, societal perceptions of nuclear science have gone through several distinct periods. As a long-established reactor in a residential area, the MNR is a useful case study showing how global events and scientific developments can shift public opinion. Using meeting notes, speech transcripts, and newspaper articles from the McMaster archives and online databases, the image of nuclear research in society can be compared between decades. These sources consistently described the same benefits of nuclear research at McMaster throughout its history, namely its benefits for education, medical research, and its relative safety. However, the factors which received the most focus changed as global support for nuclear research fluctuated. Upon its inception, the MNR benefitted from a global interest in nuclear science and its potential for education was deemed exciting. After the nuclear disasters at Three Mile Island in 1979 and Chernobyl in 1986, constant reminders about safety mechanisms at the MNR eased paranoia. When the future of the MNR was in question in the 1990s, its isotope production for cancer treatments became instrumental in keeping it operational. The effectiveness of these arguments is paramount for researchers today as McMaster continues its research into Small Modular Reactors, which may be used to generate energy in similar residential environments.
Keywords: McMaster; nuclear reactor; science history; science communication